Characterization of Two Novel Bacteriophages Infecting Multidrug-Resistant (MDR) Acinetobacter baumannii and Evaluation of Their Therapeutic Efficacy in Vivo - Cha, Kyoungeun; Oh, Hynu K.; Jang, Jae Y.; Jo, Yunyeol; Kim, Won K.; Ha, Geon U.; Ko, Kwan S.; Myung, Heejoon (Frontiers in Microbiology, 2018)
Acinetobacter baumannii is emerging as a challenging nosocomial pathogen due to its rapid evolution of antibiotic resistance. We report characterization of two novel bacteriophages, PBAB08 and PBAB25, infecting clinically isolated, multidrug-resistant (MDR) A. baumannii strains. Both phages belonged to Myoviridae of Caudovirales as their morphology observed under an electron microscope. Their genomes were double stranded linear DNAs of 42,312 base pairs and 40,260 base pairs, respectively. The two phages were distinct from known Acinetobacter phages when whole genome sequences were compared. PBAB08 showed a 99% similarity with 57% sequence coverage to phage AB1 and PBAB25 showed a 97% similarity with 78% sequence coverage to phage IME_AB3. BLASTN significant alignment coverage of all other known phages were less than 30%. 76 and 70 genes encoding putative phage proteins were found in the genomes of PBAB08 and PBAB25, respectively. Their genomic organizations and sequence similarities were consistent with the modular theory of phage evolution. Therapeutic efficacy of a phage cocktail containing the two and other phages were evaluated in a mice model with nasal infection of MDR A. baumannii. Mice treated with the phage cocktail showed a 2.3-fold higher survival rate than those untreated in seven days post infection. In addition, 1/100 reduction of the number of A. baumannii in the lung of the mice treated with the phage cocktail was observed. Also, inflammatory responses of mice which were injected with the phage cocktail by intraperitoneal, intranasal, or oral route was investigated. Increase in serum cytokine was minimal regardless of the injection route. A 20% increase in IgE production was seen in intraperitoneal injection route, but not in other routes. Thus, the cocktail containing the two newly isolated phages could serve as a potential candidate for therapeutic interventions to treat A. baummannii infections.